2006
DOI: 10.17159/2078-516x/2006/v18i1a246
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder injuries in competitive swimmers in KwaZulu-

Abstract: Swimming is a popular recreational and professional sport code both locally and internationally. The South African swimming team represents South Africa at the Olympics and other world-level competitions. To ensure that these participants and those who will replace them on the world arena can function optimally, it is essential to keep them injury-free. In order to ensure that the best conditioning programmes are developed it is important to know the incidence and other related information pertaining to injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
1
1
Order By: Relevance
“…The most common diagnoses involved tendonitis (35%), muscular imbalance (29%), impingement (19%) and others (17%). Despite that our study use the same age factor as Puckree and Thomas [22] , our results were higher than 19%. for impingement injuries as it recorded 37.7 %.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…The most common diagnoses involved tendonitis (35%), muscular imbalance (29%), impingement (19%) and others (17%). Despite that our study use the same age factor as Puckree and Thomas [22] , our results were higher than 19%. for impingement injuries as it recorded 37.7 %.…”
Section: Discussioncontrasting
confidence: 64%
“…The findings of Troup et al [21] showed that the rate of incidence in shoulder pain is higher in males (70%) than in females (65%), while in our study all participant suffered from shoulder pain with different intensities and the rate of subacromial injury was slightly higher in females. In the other hand Puckree and Thomas [22] studied swimmers with shoulder pain irrespective of gender or race, for the age bracket of 13-25 years. A randomized sample involving about 96 athletes were invited to join from 300 registered swimmers, and they found that 71% of the swimmers had shoulder pain 64% out of them are reported with shoulder injury.…”
Section: Discussionmentioning
confidence: 99%